2020
DOI: 10.3390/molecules25194497
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Nanoparticles as a Carrier of β-Carotene: Production, Characterisation and In Vitro Gastrointestinal Digestion

Abstract: β-carotene loaded bio-based nanoparticles (NPs) were produced by the solvent-displacement method using two polymers: zein and ethylcellulose. The production of NPs was optimised through an experimental design and characterised in terms of average size and polydispersity index. The processing conditions that allowed to obtain NPs (<100 nm) were used for β-carotene encapsulation. Then β-carotene loaded NPs were characterised in terms of zeta potential and encapsulation efficiency. Transmission electron micros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…Thus, it reduced the final extent of lipid digestion in the small intestine, as well as decreased the bio accessibility of the encapsulated carotenoids. The same trend was observed by Afonso et al (2020), and concluded that zein NPs are better carriers of β-carotene than ethyl cellulose, for crossing GIT conditions. Thus, the compounds used to produce the particles have huge impact in their stability, dictating their successful bioavailability in the intestinal phase.…”
Section: Nps Digestionsupporting
confidence: 85%
“…Thus, it reduced the final extent of lipid digestion in the small intestine, as well as decreased the bio accessibility of the encapsulated carotenoids. The same trend was observed by Afonso et al (2020), and concluded that zein NPs are better carriers of β-carotene than ethyl cellulose, for crossing GIT conditions. Thus, the compounds used to produce the particles have huge impact in their stability, dictating their successful bioavailability in the intestinal phase.…”
Section: Nps Digestionsupporting
confidence: 85%
“…It is of utmost importance to evaluate the bioaccessibility of a bioactive compound under simulated gastrointestinal conditions because the harsh digestive environment can decrease their bioaccessibility by inducing changes in their physicochemical properties. However, their bioaccessibility can be increased due to enhanced solubility in the gastrointestinal media due to the presence of lipid micelles . As depicted in Figure , despite the amounts of both VB9 and VBB12 released being higher in their free form than those observed for encapsulated compounds, the bioaccessibility of the molecules at the end of the study significantly increased when encapsulated ( p < 0.05).…”
Section: Resultsmentioning
confidence: 92%
“…Afonso et al. (2020) reported that this technique has been used to encapsulate β‐carotene in polymers as ethylcellulose (particle size: 60 nm, encapsulation efficiency: 74%) and zein (particle size: 83 nm, encapsulation efficiency: 93%).…”
Section: Stability Of Natural Food Colorantsmentioning
confidence: 99%
“…The most widely used nanoencapsulation methodology applied to carotenoids is nanoprecipitation (Fuenmayor et al, 2021). Afonso et al (2020) reported that this technique has been used to encapsulate β-carotene in polymers as ethylcellulose (particle size: 60 nm, encapsulation efficiency: 74%) and zein (particle size: 83 nm, encapsulation efficiency: 93%).…”
Section: Carotenoidsmentioning
confidence: 99%